Pattern of Injuries in Deaths by Electrocution: An Autopsy Study - Kiran , J V K; Jemila , S; Aruna , M V (Journal of Indian Academy of Forensic Medicine, 2023)
Electrical injuries are complex and associated with high morbidity and mortality. Low voltage injuries cause less severe injuries but are highly fatal whereas high voltage injuries cause more severe skin injuries. In this study we tried to analyse the pattern of injuries from electrocution in relation to the voltage the victim was exposed to. We categorized the exposure according to the voltage and place of exposure into household setup, exposure at construction site and exposure to electric utility poles and exposure to transformers. The maximum number of cases were in the category of electric utility pole exposure. The cases which occurred in a span of about one year were considered and were few in number. The findings that we got in this study were in agreement with some of the previous studies by other observers but due to low sample size further studies would help in reaching more definitive conclusions.